PERHITUNGAN SISTEM BAGI HASIL SIMPANAN DAN PINJAMAN NASABAH - Darmawan Darmawan (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
The results showed that the big difference in revenue sharing system between deposits and borrowed funds in BMT Fauzan Azhiima Parepare, which is where the formula for the result of savings is the average balance divided by total average balance multiplied by 20% of income BMT, while the formula for the proceeds of the loan is income net customers divided according to the ratio between BMT and the customer agreement. Can be seen in 2009, the income of the BMT Rp. 22,161,294. So for the results obtained customer deposits in 2009 was Rp. 22,161,294 x 20% = Rp. 4432258.8. As for the results obtained loan customers in 2009 for the owner of Rp. 6648388.2 and fund manager Rp. 15,512,905.8.